Contract documentation for contractors / Vincent Powell-Smith, John Sims and Christopher Dancaster. - Powell-Smith, Vincent (Blackwell Science, 2000)
This practical guide to contract documentation provides a set of standard letters, notices and forms for use with JCT 80, the Intermediate Form, Minor Works Form and related subcontracts.